Ocimum campechianum Mill. from Amazonian Ecuador: Chemical Composition and Biological Activities of Extracts and Their Main Constituents (Eugenol and Rosmarinic Acid) - Massimo Tacchini; Monica Paulina Echeverria Guevara; Alessandro Grandini; Immacolata Maresca; Matteo Radice; Letizia Angiolella; Alessandra Guerrini (Molecules, 2020)
The essential oil (EO), the methanolic (MeOH), and the 70% ethanolic (70% EtOH) extracts obtained from the aerial parts of Ocimum campechianum Mill. (Ecuador) were chemically characterized through gas-chromatography coupled to mass spectrometry detector (GC-MS), high-performance liquid chromatography coupled to diode array-mass spectrometry detectors (HPLC-DAD-MS) and studied for their in vitro biological activity. The radical scavenger activity, performed by spectrophotometric 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays, highlighted significant IC50 values for the EO, extracts and their main constituents (eugenol and rosmarinic acid). EO (and eugenol) showed noteworthy activity against Pseudomonas syringae pv. syringae and a moderate effect against clinical Candida strains, with possible synergism in association to fluconazole against the latter microorganisms. The extracts and pure molecules exhibited weak cytotoxic activity against the HaCat cell line and no mutagenicity against Salmonella typhimurium TA98 and TA100 strains, giving indication of safety. Instead, EO showed a weak activity against adenocarcinomic human alveolar basal epithelial cells (A549). The above-mentioned evidence leads us to suggest a potential use of the crude drug, extracts, and EO in cosmetic formulation and food supplements as antioxidant agents. In addition, EO may also have a possible application in plant protection and anti-Candida formulations.